2016
DOI: 10.3390/nu8100608
|View full text |Cite
|
Sign up to set email alerts
|

The VITAH Trial—Vitamin D Supplementation and Cardiac Autonomic Tone in Patients with End-Stage Kidney Disease on Hemodialysis: A Blinded, Randomized Controlled Trial

Abstract: End-stage kidney disease (ESKD) patients are at increased cardiovascular risk. Vitamin D deficiency is associated with depressed heart rate variability (HRV), a risk factor depicting poor cardiac autonomic tone and risk of cardiovascular death. Vitamin D deficiency and depressed HRV are highly prevalent in the ESKD population. We aimed to determine the effects of oral vitamin D supplementation on HRV ((low frequency (LF) to high frequency (HF) spectral ratio (LF:HF)) in ESKD patients on hemodialysis. Fifty-six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Although only 2 patients presented SDNN under 50 ms in the present study, the mean 24 h SDNN of this study population was 84 ms; considered to be moderately depressed. This finding is consistent with other published studies reporting depressed HRV in haemodialysis patients [ 6 , 8 , 18 , 38 , 40 , 41 , 42 , 43 ]. Effects of medication on HRV should be considered in this poly-medicated patient population.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although only 2 patients presented SDNN under 50 ms in the present study, the mean 24 h SDNN of this study population was 84 ms; considered to be moderately depressed. This finding is consistent with other published studies reporting depressed HRV in haemodialysis patients [ 6 , 8 , 18 , 38 , 40 , 41 , 42 , 43 ]. Effects of medication on HRV should be considered in this poly-medicated patient population.…”
Section: Discussionsupporting
confidence: 94%
“…This study confirms previous reports that HRV is substantially reduced in haemodialysis patients compared to healthy controls [36,37] and extends these findings by demonstrating consistently that time-domain and frequency-domain HRV parameters were significantly lower in haemodialysis patients compared to age-, sex-and BMI-matched healthy controls. Patients in this study also had SDNN measurements amongst the lowest reported in comparison to other haemodialysis cohorts [6,8,18,38]. This might be related to the fact that these were patients that recently started haemodialysis (measurements taken between 6 and 10 weeks of commencing treatment).…”
Section: Discussionmentioning
confidence: 64%
“…Entretanto, só houve elevação nesta relação nos indivíduos que permaneceram com vitamina D sérica insuficiente, mesmo após suplementação intensiva por seis semanas. 36 De forma semelhante, este ensaio encontrou proteção vagal após a suplementação da vitamina D, pela elevação significativa do tônus parassimpático. Adicionalmente, esses achados se corroboraram, de forma consistente, pela redução significativa do tônus simpático.…”
Section: Discussionunclassified
“…Because vitamin D3 has versatile therapeutic efficacies on cardiovascular diseases [142], vitamin D3 may have an impact on SUDEP [143]. Although there is no direct evidence demonstrating a possible role for vitamin D in SUDEP prevention, one group has reported that vitamin D supplementation can modulate HRV [144,145,146,147], which is frequently lower in patients with drug-refractory epilepsy, a group at high risk of SUDEP [148,149]. This raises the possibility that vitamin D may have therapeutic benefits for the prevention of SUDEP.…”
Section: Functional Nutrients Beneficial In Epilepsymentioning
confidence: 99%